Adolescent elite Kenyan runners are at risk for energy deficiency, menstrual dysfunction and disordered eating - Muia, E. N.; Wright, H.; Onywera, V. O.; Kuria, E. N. (Journal of Sports Sciences, 2016)
Limited data are available on the female athlete triad (Triad) in athletes from minority groups. We explored subclinical and clinical Triad components amongst adolescent elite Kenyan athletes (n = 61) and non-athletes (n = 49). Participants completed demographic, health, sport and menstrual history questionnaires as well as a 5-day weighed dietary record and exercise log to calculate energy availability (EA). Ultrasound assessed calcaneus bone mineral density (BMD). Eating Disorder Inventory subscales and the Three-Factor Eating Questionnaire`s cognitive dietary restraint subscale measured disordered eating (DE). EA was lower in athletes than non-athletes (36.5 ± 4.5 vs. 39.5 ± 5.7 kcal · kg FFM/d, P = 0.003). More athletes were identified with clinical low EA (17.9% vs. 2.2%, OR = 9.5, 95% CI 1.17-77, P = 0.021) and clinical menstrual dysfunction (32.7% vs. 18.3%, x2 = 7.1, P = 0.02). Subclinical (75.4% vs. 71.4%) and clinical DE (4.9% vs. 10.2%, P = 0.56) as well as BMD were similar between athletes and non-athletes. More athletes had two Triad components than non-athletes (8.9% vs. 0%, OR = 0.6, 95% CI 0.5-6.9, P = 0.05). Kenyan adolescent participants presented with one or more subclinical and/or clinical Triad component. It is essential that athletes and their entourage be educated on their energy needs including health and performance consequences of an energy deficiency.